QSAR and Ab Initio studies of quinolon-4(1H)-imine derivatives as antimalarial agents - Jafar La Kilo; Akram La Kilo; Saprini Hamdiani (Acta Chimica Asiana, 2021)
Malaria is still the most dangerous disease threat in the world, including in Indonesia. In Indonesia, it is estimated that there are 20 million cases of malaria per year. Malaria resistance to conventional drugs requires the search for new antimalarial drugs. Molecular modeling can be a solution to these problems. An activity study of 22 quinolone-4 (1H) -imine derivatives as antimalarials was carried out using the QSAR Quantitative Structure-Activity Relationship method. The electronic and molecular descriptors were obtained from the Hartree-Fock HF / 6-31G ab initio calculation. The multiple linear regression (MLR) method was used to construct the QSAR model. The best QSAR models produced are: pEC50 = -4,177 + (37,902 x qC3) + (171,282 x qC8) + (9,061 x qC10) + (125,818 x qC11) + (-149,125 x qC17) + (191,623 x qC18), with statistical parameters, n = 22; r2 = 0,910; SEE = 0,171; Fhit/Ftab = 4,510 dan PRESS = 0,697. The best QSAR equation model can be used as a reference for designing and predicting the antimalarial activity of Quinolon-4 (1H) -imine derivatives which have higher activity than the previous one